The way it's never been done before my friendship with Marlon Brando - Englund, George 1926-2017 (HarperEntertainment, 2004)
Traces the life and career of Marlon Brando, remembered by his long-time friend and producer-director George Englund.
Keywords: aBrando, Marlon; aEnglund, George -- d1926-; Brando, Marlon -- 1924-2004; Filmacteurs; aMotion picture actors and actresses -- zUnited States -- vBiography; Biografie